Significantly enhanced dielectric and energy storage performance of blend polymer-based composites containing inorganic 3D–network. (15th March 2018) - Zhang, Zheng; Luo, Suibin; Yu, Shuhui; Guan, Zhishu; Sun, Rong; Wong, Ching-Ping
Abstract: Flexible nanocomposites with high permittivity (εr ), low loss and high voltage breakdown strength (Eb ) are highly desired in microelectronics and electric power systems etc. In order to obtain high energy storage performance, high values of εr and Eb should be achieved simultaneously. Balance between the εr and Eb has been challenged by their inverse behavior relating to filler content. In this study, by constructing a three dimensional-network of high-εr BaTiO3 (3D BT) ceramic fillers in the polyvinylidene fluoride (PVDF)-epoxy blend polymer matrix, an ultra-high permittivity of 292 and a low loss of less than 0.1 were obtained with 31 vol% inorganic fillers. Meanwhile, the energy storage density was enhanced by more than 3 times in comparison with the PVDF-epoxy polymer matrix. Graphical abstract: Image 1 Highlights: High permittivity of 292 and low loss obtained at a low filler loading of 31 vol% Demonstrating the highest permittivity value in the ever reported polymer-based composites Significantly enhanced energy storage performance of polymer-based composite